Proyecto de factibilidad para la implementación de una empresa productora de brochetas de frutas congeladas bañadas de chocolate y su comercialización en la provincia de Morona Santiago - Castañeda Merino, Mirian Estela (2015)
The objective of this research is to determine the feasibility of creating a company producing skewers frozen fruit dipped in chocolate and commercialization in the province of Morona Santiago which allowed the application of different methods and techniques that research allows, as the deductive method, the inductive method which the particular part to reach usually the Statistical Method which consists of a set of procedures for managing qualitative and quantitative research data. This data management purpose is to check, in a part of the reality of one or more vertical consequences deduced from the general and specific objectives of the research. The use of these methods allowed to reach the culmination of this work and that to do had to follow the steps of understanding and application of the same show. In the market study in the province of Morona Santiago, with a sample of 399 families; Weighted surveys have been analyzed and the results have been inferred and then perform market analysis, determining the potential demand of 88,292 families, 83,877 families real demand, effective demand 57,875 families who buy frozen fruit skewers 2,778,021 bathed in chocolate, offering 298,704 frozen fruit skewers dipped in chocolate and unmet 2479317 frozen fruit skewers dipped in chocolate, which allowed us to determine that the project can and should be performed by the results obtained in the analysis of demand, supply and levels of marketing this product. The installed capacity of the project determines that the company will be able to produce 83,200 frozen fruit skewers dipped in chocolate and with a capacity of 49,920 will be used frozen fruit skewers dipped in chocolate, of which 60% of the capacity is used to produce the first year, and the location thereof to be located in the city of Palora, streets and Cuenca Passage Riofrio is determined. The production process requires the use of suitable equipment, which will be guaranteed to get a quality product at reasonable prices. Then determining the project engineering process diagrams, characteristics of operation and management, technical requirements as equipment, facilities, furniture and fixtures develops. Also an administrative study determined as a Limited Liability Company, and functional organizational structure to both hierarchical levels Legislative, executive, consultant level, auxiliary or support level, operational level, as well as operating manuals, charts was performed ; which served as a guideline for implementing a good organization, because it will have the following staff: Manager, a Secretariat Contadora a Concierge-Keeper, who will be part of the Administrative staff and operational staff distributed as follows: a Chief production, Two Workers, and a seller. The project reaches an investment of $ 52,636.64 and will be funded with contributions from partners the 52.50% of total investment corresponding to $ 27,636.32 and a loan to keep the project with the Development Bank will be the corresponding to 47.50% $ 25,000 5-year term at 15% annual interest. The financial evaluation shows the following results: According to the NPV of this project gives a positive value of $ 51,453.64, indicating that the project or investment is suitable. For this project, the IRR is 35.95% and this value satisfactory to carry out the project, the time required to recover the initial investment would be 3 years, 9 months and 18 days to this project, the sensitivity values are less than one, therefore not affect changes in project costs and revenues increased 23.9% and decreased by 17.10%, respectively, ie the project is not sensitive to these changes. Then the most significant findings and recommendations of the project is proposed